AKTIVITAS HATI TIKUS (RATTUS SP) YANG DIBERI RANSUM MENGANDUNG TEPUNG DAUN KALIANDRA (Calliandra calothyrsus) DAN KULIT NANAS (Ananas comosus) SELAMA MASA PERTUMBUHAN - SETYAWATI, IRIANI; DEWANTARA PUTRA, I GUSTI NGURAH AGUNG; RONI, NI GUSTI KETUT (Jurnal Biologi Udayana, 2017)
Calliandra calothyrsus leaves contain 17-28% protein thus potential as a protein source in animal diet. However, it also contain a high antinutrition of condensed tannins (>10%). The addition of protease enzymes (bromelain) in the diet containing tannins is expected to overcome the negative effects of tannins. Bromelain can be obtained from the pineapple plant (Ananas comosus) including the peel. This study was a feeding experiment on weaned male and female rats during the growth period. This study used a completely randomized design of 4x4 factorial design. The main factor was Calliandra leaf meal substitution levels of 0; 10; 17.5 and 25% in the diet. The sub factor was pineapple peel additive levels of 0; 4.35; 8.70 and 13.05 g/rat/day. Weaned rats were divided into 16 groups and they were fed for two months during growth period. The study showed that there was no interaction between calliandra leaves and pineapple peels on the rat liver activity including the blood levels of SGOT and SGPT levels. SGPT and SGOT levels were not affected by all levels of pineapple peels in the diets. All calliandra levels did not affect the level of SGOT, but 17.5 and 25% calliandra in the diets increased SGPT level.